Factors Fuelling Child Prostitution in Kisenyi Slum, Kampala - Kisambira Moses (Kampala : Uganda Christian University, 2009)
Descriptive cataloguing Dissertation (CDCM) Uganda Christian University Mukopno.
Includes Bibliographical Referencies (p.30) ang Appendices (p. 31-36)
Keywords: Children and Prostitution